Further Evidence That N2pc Reflects Target Enhancement Rather Than Distracter Suppression - Li, Chaojie; Liu, Qiang; Hu, Zhonghua (Frontiers in Psychology, 2018)
The N2pc component is an index to explore the covert mechanism of visual-spatial attention. The N2–posterior–contralateral (N2pc) component is an index in the domain of event-related potentials (ERPs) for exploring the underlying mechanism of visual-spatial attention. It has been controversial disputed whether the attentional selection reflected by the N2pc was primarily due to distractordistracter suppression or target enhancement processes. We addressed this controversy by combining the pop-out item and the target feature, and instructed to participants whether the pop-out item included the target feature. Thus, Iin a visual search task, we presented a bilateral visual display containing a pop-out item and three distractor items. bilateral visual stimuli including a pop-out item and three distractors were displayed simultaneously. The pop-out detection was analyzed under varying two factors: (a) pop–out item as a target or non-target (b) the distractor itemsdistractors contain a target feature or non-target feature. Although all conditions had a salient effect on behavioral performance, the reliable difference of N2pc only existed between target condition and non-target condition. These results provided strong support for the hypothesis of target enhancement processes.